Roles of 21 Genera of Human Gut Microbiota in Barrett’s Esophagus Risk: A Mendelian Randomization Study - Yang, Zhao; Yu, Rong; Deng, Wei; Wang, Weihu (Frontiers in Genetics, 2022)
Background: Lacking of definitive evidence supports the putative hypothesis that gut microbiota dysbiosis is associated with Barrett’s Esophagus (BE). We conducted a two-sample Mendelian randomization study to assess the associations of 21 genera of human gut microbiota with BE. Methods: We identified independent genetic instruments for 21 genera of gut microbiota (including nine dominant genera, four core genera among individuals of European ancestry, and eight esophagus-specific genera of gut microbiota) from MiBioGen (up to 18,340 participants). We applied them to summary statistics from the largest publicly available genome-wide association study on BE (9,680 cases and 31,211 controls). We obtained the causal estimates of genetically predicted higher genera of gut microbiota and BE using the inverse variance weighting method. Sensitivity analyses included weighted median, MR-Egger, MR-RAPS, and MR PRESSO. Results: We found that genetically predicted higher Actinomyces (OR: 0.76 per-unit increase in log odds of having BE, 95% CI: 0.70 to 0.83) and higher Ruminiclostridium (OR: 0.75, 95% CI: 0.63 to 0.90) were significantly associated with a lower risk of BE. No associations of other genera of gut microbiota with BE were noted, apart from suggestive associations of higher Alistipes (OR: 0.77; 95% CI: 0.61 to 0.99), higher Eubacterium (OR: 0.89; 95% CI: 0.80 to 0.99), higher Veillonella (OR: 0.76; 95% CI: 0.56 to 1.02) with a lower risk of BE, and higher Faecalibacterium (OR: 1.15; 95% CI: 0.99 to 1.33) with a higher risk of BE. Conclusion: This study suggests that higher Actinomyces and higher Ruminiclostridium might protect against BE.